Eksistensi Hukum Acara Perdata dalam Penyelesaian Perselisihan Hak tentang Upah pada Pekerja Honorer di Indonesia - Ferricha, Dian (Departemen Hukum Perdata, 2018)
Rights disputes often occur in employment relationships in various sectors, mainly related to wages. Where wages are the pulse of workers and as a form of reward for work carried out on orders from superiors. Workers who are weak in their current bargaining power that has not been resolved legally and whose energy is still needed in the work of the public sphere both government, health and education are honorary workers. Where honorary workers are workers who are appointed by stafï¬ng ofï¬cials or other ofï¬cials in the government to carry out certain tasks in government agencies that are paid voluntarily through contractual agreements or in the form of decrees. In the legal aspect, they have no clear protection, are categorized as workers in industrial relations or are workers shaded by the state civil service law. This is a legal vacuum in its protection. Not to mention, when they demanded their rights in the form of wages paid below the district or provincial minimum wage standards. This is what was raised in this article because if it is not resolved when the problem is resolved through litigation, the legal basis used is not only the law on industrial relations disputes in the industrial relations court but also based on civil procedural law in the general court. This article uses a normative juridical method are based on legal materials that are normative-prescriptive. This article is very interesting to study more deeply and for this article it was created to recommend legal breakthroughs on problems that occur, one of which offers clause clauses in civil procedural law to order parties to disclose documents during the veriï¬Â cation process when settling rights on wages to workers honorary is brought into the realm of litigation, wherein one of the articles of the Industrial Relations Dispute Settlement Act it is stated that what applies in Industrial Relations Disputes is ordinary civil procedural law unless otherwise stipulated.